Work function of graphene multilayers on SiC(0001). (13th January 2017) - Mammadov, Samir; Ristein, Jürgen; Krone, Julia; Raidel, Christian; Wanke, Martina; Wiesmann, Veit; Speck, Florian; Seyller, Thomas
Abstract: The work function and electronic structure of epitaxial graphene as well as of quasi-freestanding graphene multilayer samples were studied by Kelvin probe and angle resolved photoelectron spectroscopy. The work function converges towards the value of graphite as the number of layers is increased. Thereby, n-type doped epitaxial graphene layers have a work function lower than graphite and p-type doped quasi-freestanding graphene layers exhibit a work function higher than graphite. We explain the behaviour by the filling of the π -bands due to substrate interactions.